REHABILITASI BAGI PECANDU NARKOTIKA OLEH POLDA METRO JAYA UNTUK MENEKAN PEREDARAN GELAP NARKOTIKA DI JAKARTA - Armunanto Hutahaean; Situmorang, Dina Agustina (Jurnal Hukum to-ra : Hukum Untuk Mengatur dan Melindungi Masyarakat, 2023)
Narcotics become an extraordinary threat for human life. The development of drugs trafficking is very fast due to the increasing number of users or addicts. Nowadays, based on data from National Narcotics Agency (BNN), there are almost five million narcotics addicts in Indonesia. These narcotics addicts are mostly spread in big cities such as Jakarta, Surabaya, Medan, Makassar and Bandung. Jakarta as the capital city of Indonesia, center of economy, trade and business is the city with the largest population of narcotics addicts. There are so many narcotics dealers carry out their illicit actions in Jakarta. It can be confirmed that there are always narcotics dealers in every subdistrict. The narcotics dealers do not stop offering these illicit narcotics to buyers who come timeless. Even the law enforcement seems unable to suppress the narcotics traficking. In fact, it often happens that the narcotics users change their status to be narcotics dealers after the law enforcements are conducted by the law enforcement officials. Therefore,it is neccessary to find the right solutions to suppress the drugs trafficking so that it does not become a very dangerous threat anymore namely by decreasing the narcotics user, one of the right ways is rehabilitation for the narcotics users.